"Walking in a maze": community providers' difficulties coordinating health care for homeless patients. Issue 1 (December 2016) - LaCoursiere Zucchero, Terri; McDannold, Sarah; McInnes, D.
Abstract Background While dual usage of US Department of Veterans Affairs (VA) and non-VA health services increases access to care and choice for veterans, it is also associated with a number of negative consequences including increased morbidity and mortality. Veterans with multiple health conditions, such as the homeless, may be particularly susceptible to the adverse effects of dual use. Homeless veteran dual use is an understudied yet timely topic given the Patient Protection and Affordable Care Act and Veterans Choice Act of 2014, both of which may increase non-VA care for this population. The study purpose was to evaluate homeless veteran dual use of VA and non-VA health care by describing the experiences, perspectives, and recommendations of community providers who care for the population. Methods Three semi-structured focus group interviews were conducted with medical, dental, and behavioral health providers at a large, urban Health Care for the Homeless (HCH) program. Qualitative content analysis procedures were used. Results HCH providers experienced challenges coordinating care with VA medical centers for their veteran patients. Participants lacked knowledge about the VA health care system and were unable to help their patients navigate it. The HCH and VA medical centers lacked clear lines of communication. Providers could not access the VA medical records of their patients and felt this hampered the quality and efficiency of care veterans received. Conclusions Substantial challenges exist in coordinating care for homeless veteran dual users. Our findings suggest recommendations related to education, communication, access to electronic medical records, and collaborative partnerships. Without dedicated effort to improve coordination, dual use is likely to exacerbate the fragmented care that is the norm for many homeless persons.